Anhedonia and cognitive function in adults with MDD: results from the International Mood Disorders Collaborative Project. (30th December 2015) - McIntyre, Roger S.; Woldeyohannes, Hanna O.; Soczynska, Joanna K.; Maruschak, Nadia A.; Wium-Andersen, Ida K.; Vinberg, Maj; Cha, Danielle S.; Lee, Yena; Xiao, Holly X.; Gallaugher, Laura Ashley; Dale, Roman M.; Alsuwaidan, Mohammad T.; et al.
Abstract : Background: Cognitive dysfunction is common in major depressive disorder (MDD) and a critical determinant of health outcome. Anhedonia is a criterion item toward the diagnosis of a major depressive episode (MDE) and a well-characterized domain in MDD. We sought to determine the extent to which variability in self-reported cognitive function correlates with anhedonia. Method: A post hoc analysis was conducted using data from (N=369) participants with a Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, Text Revision (DSM-IV-TR)-defined diagnosis of MDD who were enrolled in the International Mood Disorders Collaborative Project (IMDCP) between January 2008 and July 2013. The IMDCP is a collaborative research platform at the Mood Disorders Psychopharmacology Unit, University of Toronto, Toronto, Canada, and the Cleveland Clinic, Cleveland, Ohio. Measures of cognitive function, anhedonia, and depression severity were analyzed using linear regression equations. Results: A total of 369 adults with DSM-IV-TR–defined MDD were included in this analysis. Self-rated cognitive impairment [ie, as measured by the Adult ADHD Self-Report Scale (ASRS)] was significantly correlated with a proxy measure of anhedonia (r=0.131, p=0.012). Moreover, total depression symptom severity, as measured by the total Montgomery–Åsberg Depression Rating Scale (MADRS) score, was also significantly correlated with self-rated measures of cognitive dysfunction (r=0.147, p=0.005). The association between anhedonia and self-rated cognitive dysfunction remained significant after adjusting for illness severity (r=0.162, p=0.007). Conclusions: These preliminary results provide empirical data for the testable hypothesis that anhedonia and self-reported cognitive function in MDD are correlated yet dissociable domains. The foregoing observation supports the hypothesis of overlapping yet discrete neurobiological substrates for these domains.